AlamCera: A Malay Folklore Mobile Game Development Based on Action Adventure Game - BINTI MOHAMAD LAZI, NUR ALYA ADLINA; BINTI SENAN, NORHALINA (Applied Information Technology And Computer Science, 2025)
Malay folklore are traditional stories and legends, spread by the Malays as a teaching medium that is currently delivered to society through oral storytelling, books, e-books and animation. However, there is a lack of interactive games based on Malay folklore available on the market. Thus, AlamCera is proposed to consist of four levels based on popular folktales including Sang Kancil, Mat Jenin, Batu Belah Batu Bertangkup and Sang Kelembai. Using a 2D pixel art style and side-scrolling gameplay, with action adventure elements such as battling enemies and completing quests to advance the story. The Game Development Life Cycle (GDLC) methodology is utilized with development tools like Aseprite and Unity to build on the Android mobile platform. The testing result from the System Usability Scale shows a 68.3 score which indicates that the game’s gameplay and overall usability experience is good to the majority of users.